2007
DOI: 10.1371/journal.pone.0000280
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adherence to Anti-Hypertensive Treatment in Pakistan

Abstract: ObjectivesPoor adherence is one of the biggest obstacles in therapeutic control of high blood pressure. The objectives of this study were (i) to measure adherence to antihypertensive therapy in a representative sample of the hypertensive Pakistani population and (ii) to investigate the factors associated with adherence in the studied population.Methods and ResultsA cross-sectional study was conducted on a simple random sample of 460 patients at the Aga Khan University Hospital (AKUH) and National Institute of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
190
12
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(261 citation statements)
references
References 31 publications
35
190
12
5
Order By: Relevance
“…Similarly in an Iranian study by Hadi (2004) older patients were more and in a study from Iraq, the compliance was highest among patients aged 70 years and more (78%) followed by those <30-year-old (64%), and females were significantly more compliant than males. 22,24 Another study carried out in Pakistan among 460 hypertensive, showed that adherence increases with age and highest mean adherence rate was in the age group of 70-80 years. 23 Our study showed significant association with gender and marital status to the level of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in an Iranian study by Hadi (2004) older patients were more and in a study from Iraq, the compliance was highest among patients aged 70 years and more (78%) followed by those <30-year-old (64%), and females were significantly more compliant than males. 22,24 Another study carried out in Pakistan among 460 hypertensive, showed that adherence increases with age and highest mean adherence rate was in the age group of 70-80 years. 23 Our study showed significant association with gender and marital status to the level of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies shown no association of compliance with age and sex, but for literacy. 25 The present study has shown significant increase in compliance scores of all study subjects as well as in case of compliant and non-compliant patients after educating the patients about hypertension (Table 2, Figure 1) 19,20,21,[26][27][28][29] One study however could not find significant effect of education of hypertensive patients through mailing education packets, on mildly uncontrolled hypertension, but significant improvement in patient knowledge, home monitoring and satisfaction was observed. 30 In our study one to one verbal communication in the language of the patient probably proved more beneficial in improving compliance.…”
Section: Discussionmentioning
confidence: 67%
“…Baune et al, 26 showed a significant correlation between education and quality of life (QOL) among patients with hypertension in Gaza Strip and hypothesized that educational interventions would be essential in preventing high blood pressures and consequent mortality. Knowledge of hypertension significantly affected adherence in Hashmi et al 27 study sample. Patients who were aware of the association between certain risk factors for hypertension, such as high salt intake, stress and a positive family history, had better adherence compared to those who with poorer knowledge.…”
Section: Discussionmentioning
confidence: 88%